The internet of women : accelerating culture change - Anid, Nada; Cantileno, Laurie; Morrow, Monique; Zafar, Rahilla (River Publishers Series in Innovation and Change in Education - Cross-Cultural Perspective Ser., 2016)
"Female scientists, technologists, engineers, and mathematicians worldwide are making historic contributions to their fields. The Internet of women provides an exciting look at personal narratives and case studies of female leaders and cultural shifts around the globe that illustrate this promising trend"--Back cover